The use of free myocutaneous flap and implant reinsertion for staged cranial reconstruction in patients with titanium mesh exposure and large skull defects with soft tissue infection after cranioplasty: Report of 19 cases. Issue 7 (2nd September 2021) - Han, Yudi; Chen, Youbai; Han, Yan; Chen, Zhaoyang; Li, Liangxing; Pu, Wenwen; Cui, Lei; Chai, Mi; Li, Yan
Abstract: Background: Management of cranial defects following failed cranioplasty due to titanium mesh exposure and infection is challenging. The purpose of this report is to describe a modified technique using a free myocutaneous flap transfer for primary soft tissue reconstruction, and titanium mesh reinsertion for cranioplasty revision. Methods: Nineteen patients with titanium mesh exposure and infection following cranioplasty were treated from January 2012 to January 2019. The average patient age was 41.89 years and the average size of the cranial defect was 7.74 × 13.92 cm. The reasons for craniotomy were craniocerebral trauma ( n  = 17), cerebrovascular disease ( n  = 1), and brain tumor ( n  = 1). The mean duration between implant exposure and current procedure was 7.16 months. Implant was removed and a free myocutaneous flap was designed to cover both scalp and cranium defects. After a mean duration of 12.32 months, implants were re‐inserted in a vascularized pocket at the second stage by elevating a plane between the previously transferred fascia layer and muscle layer. Results: The average sizes of the muscle flaps and skin paddles were 7.74 × 13.92 cm and 4.97 × 8.97 cm. The average size of the implants was 8.24 × 14.42 cm. All flaps survived completely with no complication. After an average follow‐up of 48.16 months there were no cranioplasty failures. Functional coverage of craniectomy defect sites with normalized head contour was achieved. Conclusions: The use of free myocutaneous flap and implant reinsertion achieved durable cranial and scalp defect reconstruction and aesthetic outcomes. The myocutaneous flap increases blood supply to the scalp, which may reduce the chances of infection and implant re‐exposure.